Karakteristik Perusahaan dan Pengungkapan Keanekaragaman Hayati (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2019) - Dzikirullah, Afirmatif (Fakultas Ekonomi Universitas Samudra, 2023)
The research was conducted with the aim of identifying the relationship between company characteristics and biodiversity disclosure in manufacturing, plantation and mining companies in Indonesia in the 2017-2019 period. The total number of samples used is 71 companies. Factors that characterize the company in this study include company size, company age, profitability, leverage, and operational scope. The research method used is a quantitative method. The findings from this study indicate that operational coverage has a positive influence on the level of biodiversity disclosure. Meanwhile, profitability and leverage have a negative effect on the level of disclosure. The results of this study can provide guidance for companies to pay more attention to aspects of biodiversity and establish mutually beneficial relationships in sustainability efforts.